Formulations to overcome the divergence of iterative method of fixed-point in nonlinear equations solution (2023)
When we need to determine the solution of a nonlinear equation there are two options: closed-methods which use intervals that contain the root and during the iterative process reduce the size of natural way, and, open-methods that represent an attractive